Topical and cutaneous delivery using nanosystems - Roberts, M.; Mohammed, Y.; Pastore, M.; Namjoshi, S.; Yousef, S.; Alinaghi, A.; Haridass, I.; Abd, E.; Leite-Silva, V.; Benson, Heather; Grice, J. (Elsevier, 2017)
The goal of topical and cutaneous delivery is to deliver therapeutic and other substances to a desired target site in the skin at appropriate doses to achieve a safe and efficacious outcome. Normally, however, when the stratum corneum is intact and the skin barrier is uncompromised, this is limited to molecules that are relatively lipophilic, small and uncharged, thereby excluding many potentially useful therapeutic peptides, proteins, vaccines, gene fragments or drug-carrying particles. In this review we will describe how nanosystems are being increasingly exploited for topical and cutaneous delivery, particularly for these previously difficult substances. This is also being driven by the development of novel technologies, which include minimally invasive delivery systems and more precise fabrication techniques. While there is a vast array of nanosystems under development and many undergoing advanced clinical trials, relatively few have achieved full translation to clinical practice. This slow uptake may be due, in part, to the need for a rigorous demonstration of safety in these new nanotechnologies. Some of the safety aspects associated with nanosystems will be considered in this review.